A single crystalline porphyrinic titanium metal–organic framework1. Issue 7 (15th July 2015) - Yuan, Shuai; Liu, Tian-Fu; Feng, Dawei; Tian, Jian; Wang, Kecheng; Qin, Junsheng; Zhang, Qiang; Chen, Ying-Pin; Bosch, Mathieu; Zou, Lanfang; Teat, Simon J.; Dalgarno, Scott J.; et al.
<x xml:space="preserve">Abstract</x> We have successfully synthesized a single crystalline porphyrinic titanium MOF, namely PCN-22. PCN-22 represents an important step towards mimicking dye sensitized TiO2 in MOFs.